Mechanism of microstructure and mechanical properties improvement through ultrasonic rolling pressing layer-by-layer and adaptive ultrasonic rolling method research in AlSi10Mg laser powder bed fused - Bo Qian; Peng Dai; Man Zhao; Qiyue Cui; Gang Liu; Qingsong Wei; Ruidi Li; Steven Y. Liang (Journal of Materials Research and Technology)
In the process of laser powder bed fusion (L-PBF), the high-speed movement of the laser heat source causes uneven temperature and stress fields, thus, it results in dendrites, pores, micro cracks and residual stresses. This paper explores a new process of AlSi10Mg alloy grain refinement through ultrasonic roller pressing (USRP) mechanical loading in the laser powder bed fusion layer-by-layer manufacturing process, which achieves an increase in density and improves mechanical properties. Experimental results shows that the porosity decreases to 1 %, and it presents nearly equiaxed grains with a grain size of approximately 8 μm. This improves the mechanical properties and plastic strength of the parts in the construction direction, increasing the yield strength to over 405 MPa, tensile strain to over 8 %, maximum compressive strength to over 46 %, and compressive stress to over 600 MPa. With grain refinement, strength and plasticity are both enhanced. Meanwhile, a new adaptive L-PBF-USRP method is proposed. Compared with the fixed mode, the adaptive L-PBF-USRP mode has a more uniform residual stress on the surface and a more significant stress relaxation effect. Using USRP can reduce the deformation and residual stress of the fabricated AlSi10Mg parts. This work provides a new method for designing and manufacturing high-performance alloys, especially for laser powder bed fusion processes of alloy materials.